From BMI to TMI: revisiting adiposity and fitness assessment in young active adults through a historical and contemporary lens - Yaşar, Onur Mutlu; Gürses, Veli Volkan; Ciğerci, Ali Erdem; Bal, Erdal; Pehlivan, Yeliz; Baş, Mustafa; Malkoç, Nedim; Bektaş, Merve; Başkaya, Gizem; Dündar, Sare; Karakullukçu, Ömür Fatih; Küçük, Hamza (Frontiers in Public Health, 2025)
BackgroundTraditional reliance on body mass index (BMI) to assess adiposity may misclassify physically active individuals with high lean mass. The triponderal mass index (TMI) has emerged as a potentially more accurate alternative, but evidence in physically active populations is limited.PurposeTo examine the associations of TMI and BMI with bioimpedance-derived adiposity and selected hematological markers in physically active young adults.MethodsIn this cross-sectional study, (n = 59) participants (male = 37, female = 22; age 22.63 ± 2.29 years) underwent anthropometry, whole-body bioimpedance and venous blood sampling. TMI and BMI were calculated, and associations with body fat percentage, hemoglobin, hematocrit, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were examined. Normality assumptions were checked; correlations and multiple linear regressions were computed (α = 0.05). Physical activity status followed WHO/ACSM guidelines (≥150 min·week−1 of moderate-to-vigorous activity).ResultsTMI showed a stronger positive correlation with body fat percentage than BMI (r = 0.50, p < 0.001 vs. r = 0.38, p = 0.003). BMI was positively correlated with HGB (r = 0.32, p = 0.013) and HCT (r = 0.26, p = 0.046) and negatively correlated with NLR (ρ = −0.27, p = 0.041) and PLR (r = −0.30, p = 0.022). TMI was negatively correlated with NLR (p = −0.27, p = 0.039). In the multivariable model (predictors: BMI, TMI, HGB, HCT, NLR, PLR), HCT was a significant negative predictor of adiposity (β = −0.34, p = 0.021), whereas TMI showed a positive but marginally non-significant association (β = 0.25, p = 0.073). Assumptions and multicollinearity were acceptable.ConclusionIn physically active young adults, TMI relates more strongly than BMI to bioimpedance-derived adiposity and may aid field-based screening. However, athlete-level decisions should await confirmation in sport-specific, longitudinal studies using criterion methods.